Social-Cultural Aspect in The Effort Healing of Breast Cancer Disease - Yunni Deswita (Science Midwifery, 2021)
Breast cancer is a frightening disease for people in the city of Padang. Each year there is an increase in cases of death caused by this disease. The delay of breast cancer patients in accessing treatment is the cause of the high mortality rate. Researchers try to see what causes the delay from a socio-cultural point of view. Among them are the intervention of family members (nuclear / extended family) in deciding the treatment system to be undertaken by breast cancer sufferers and the existence of a stigma against this disease. Disease etiology and the health care system are concepts used in explaining these delays.